(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The notations of strong and week forms of open sets and closed sets in the digital line and digital plane have been used in digital image filtering techniques. The purpose of this paper is to characterize tsets in Digital Topology with special reference to α – closed and α- open sets.